Hawking-Page transition in holographic QCD at finite density - Nelson R.F. Braga; Octavio C. Junqueira (Physics Letters B, 2024)
We study the confinement/deconfinement transition of QCD matter for a quark-gluon plasma at finite density using AdS/QCD duality. In order to determine the critical temperature and its dependence on the quark chemical potential, the semi-classical Hawking-Page approach is considered for a charged AdS black hole. The result obtained is consistent with the QCD phase diagram, with the critical temperature decreasing as the chemical potential increases. Using the soft wall holographic model, the value of quark density in which the phase transition occurs at zero temperature is estimated. For higher densities the QCD matter is deconfined, independent of the temperature.